Monitoring Quality and Yield Capacity of Soybean Varieties during the Creation of Various Ecotypes in Kazakhstan - Svetlana Vladimirovna Didorenko; Aigul Izteleuovna Abugaliyeva; Raushan Saylauvna Yerzhebayeva; Vladimir Gennadievich Plotnikov; Andrey Viktorovich Ageyenko (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
In 2020, on the territory of the Republic of Kazakhstan, soybeans were cultivated on an area of about 127.7 thousand hectares. To expand the acreage of this crop, it is necessary to create new varieties with a high genetic potential for productivity and quality and adaptive to the various soil and climatic zones of the Republic. The work aims to monitor the quality indicators and productivity of new highly productive varieties of soybeans with a high content of protein and oil in seeds. In Kazakhstan, 18 varieties of soybeans have been bred and approved for production at latitudes from 53 to 42°N. The varieties belong to maturity groups 00, 0, I, II, III. There is a tendency to an increase in the collection of oil and protein in the varieties of the new generation. In the varieties created in the 70s-80s, the collection of protein per hectare was 1,078.0-1,238.3 kg and oil at 577.5-734.5 kg. In the new generation varieties, the collection of protein per hectare is in the range of 944.7-1,705.3 kg, and oil at 415.9-974.6 kg. The yield capacity of different varieties falls in the range of 20.9 to 43.9 kg/ha, depending on the maturity group.